Free jejunal transplantation in a patient with short neck, cervical spondylosis, and vascular calcification: A case report - Naoki Matsuura; Yusuke Shimizu; Edward Hosea Ntege; Reiko Asato; Shohei Ishihara; Rikako Matsuura (JPRAS Open)
Total pharyngo-laryngo-esophagectomy (TPLE) with free jejunal transplantation (FJT) is the standard reconstructive procedure for hypopharyngeal cancer, typically utilizing the superior thyroid artery as the recipient vessel. However, patient-specific anatomical variations and comorbidities can significantly complicate this surgery. We present a unique case of a 68-year-old male with hypopharyngeal cancer who exhibited multiple challenges, including short stature (126 cm), low weight (35 kg), cervical spondylosis, and a history of vertebroplasty, highlighting the complexities inherent in such reconstructions.Following preoperative chemotherapy, the patient underwent TPLE and bilateral neck lymph node dissection. Due to the patient's short neck and severe calcification of the external carotid artery, the left transverse cervical artery (TCA) was selected for vascular anastomosis. A jejunal segment was harvested and precisely trimmed using indocyanine green (ICG) fluorescence imaging to optimize blood flow.The procedure was successfully completed without complications. The patient resumed oral intake two weeks postoperatively and was discharged one month after surgery. Adjuvant radiation and chemotherapy were subsequently administered. At the six-month follow-up, there was no evidence of tumor recurrence, and the patient maintained a soft food diet.This case demonstrates the effectiveness of employing the TCA and ICG fluorescence imaging in FJT for patients with complex cervical anatomy. This approach holds the potential to prevent severe complications such as tetraplegia secondary to myelopathy. To our knowledge, this is the first reported case detailing such a complex reconstruction in a patient presenting with this specific constellation of anatomical challenges. Our findings offer valuable insights for managing difficult head and neck reconstructive surgeries.